Interparental Conflict and Korean Children’s Inhibitory Control: Testing Emotional Insecurity as a Mediator - Lee, Young-Eun; Seo, SoJung (Frontiers in Psychology, 2021)
This study examined the association between interparental conflict and Korean children’s inhibitory control, and it investigated whether this relationship is mediated by the single latent variable of emotional insecurity or by three dimensions of emotional insecurity (i.e., involvement, emotional reactivity, and avoidance). A total of 166 mother–father dyads with Korean children aged 3–5 years participated in a short-term longitudinal survey at two time points. Both parents completed measures of interparental conflict and emotional insecurity, and six months later, they completed a measure of the children’s inhibitory control. The structural equation modeling results suggested that interparental conflict was related to poor inhibitory control in Korean children. Emotional insecurity did not mediate the association between interparental conflict and inhibitory control. Of the three emotional insecurity dimensions, involvement partially mediated the relationship. Interestingly, although interparental conflict predicted poor inhibitory control, the children’s involvement in the conflict, which was associated with greater interparental conflict, predicted a subsequent increase in inhibitory control six months later. These findings were interpreted in terms of sensory processing patterns, the reformulation of emotional security theory, and the influence of Confucianism on Korean culture.